Pengaruh Kepemimpinan Kepala Sekolah, Budaya Organisasi dan Reward terhadap Kepuasan Kerja Guru SD Swasta Islam Terpadu di Kota Tebing Tinggi - Zulmy Ardiansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to determine the effect of the principal's leadership, organizational culture, and rewards on the job satisfaction of teachers at the Integrated Islamic Private Elementary School in Tebing Tinggi City. This study uses a quantitative approach that aims to test the established hypothesis and analyze the effect of the independent variable on the dependent variable. The population in this study were the teachers of the Integrated Islamic Private Elementary School in Tebing Tinggi City, amounting to 129 people spread over 6 schools, while the sample taken was 98 teachers, using the proportional random sampling data collection technique. The research instrument used a questionnaire that had been tested for validity and reliability beforehand. The results showed; There is a positive and significant influence between the principal's leadership on teacher job satisfaction; There is a positive and significant influence between organizational culture on teacher job satisfaction; There is a positive and significant effect between rewards on teacher job satisfaction; There is a positive and significant influence between the principal's leadership, organizational culture and rewards together on teacher job satisfaction by 19.9%, so if these three variables increase, the teacher's job satisfaction or the dependent variable will also be better. In conclusion, there is a positive and significant influence between principal leadership, organizational culture, and rewards together on teacher job satisfaction Keywords: Organizational Culture, Principal Leadership, Teacher Job Satisfaction, Reward